2021
DOI: 10.31004/obsesi.v5i2.713
|View full text |Cite
|
Sign up to set email alerts
|

Tontonan anak di Televisi: Paradoks dan Kontestasi Nilai Tontonan Anak di Media Televisi Nasional

Abstract: Durasi dan intensitas menonton anak yang melebihi 4 jam dalam sehari akan membuat mereka  adiksi sekaligus rentan terpapar bahaya konten negatif. Penelitian ini bertujuan untuk mengetahui ragam acara anak yang tayang di media televisi nasional, mengeksplor nilai positif dan menggambarkan nilai negatif dalam program acara anak. Menggunakan pendekatan kualitatif deskriptif dengan objek penelitian pada beberapa acara anak di media televisi nasional (Trans7, MNCTV dan TVRI). Teknik pengumpulan data berupa observas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
0
10
0
3
Order By: Relevance
“…Then, Munki and Trunk's broadcast time is also too early. This also does not meet the criteria of television shows that are suitable for children according to the results of the study (Hamzah et al, 2021;Syarah et al, 2018;Wulandari & Sarmini, 2017). Si Bolang is a television show that airs on Trans 7 at 12.30 p.m. to 1.00 p.m. Si Bolang is a program that is not animated so the characters who play in this program are children not animation.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Then, Munki and Trunk's broadcast time is also too early. This also does not meet the criteria of television shows that are suitable for children according to the results of the study (Hamzah et al, 2021;Syarah et al, 2018;Wulandari & Sarmini, 2017). Si Bolang is a television show that airs on Trans 7 at 12.30 p.m. to 1.00 p.m. Si Bolang is a program that is not animated so the characters who play in this program are children not animation.…”
Section: Discussionmentioning
confidence: 93%
“…The advantages is Spongebob presents a good friendship. Then, the negative impact caused by Spongebob shows on children is that children become more hardhearted and can't concentrate or focus well (Hamzah et al, 2021;Nurnisya, 2013). This is in line with the findings found that children's television programs still contained violence, one of which was Spongebob (Rezeki, 2017;Syarief et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pengasuhan yang baik adalah pengasuhan yang dilakukan oleh kedua orang tua dengan menanamkan nilai-nilai positif pada anak (Hartanto & Yuliani, 2019;Septiani & Nasution, 2018). Penanaman nilai-nilai moral yang sifatnya untuk diri sendiri maupun sosial dirinci pada sikap dan perilaku seperti jujur, toleran, perilaku disiplin, kerjasama, mandiri, dan sebagainya (Ghufron, 2010;Hamzah et al, 2021;Makhmudah, 2020). Pengasuhan orang tua sangat penting dalam menanamkan kemandirian anak, orang tua harus lebih membuka pikiran dalam bersosialisasi, dekat dengan anak sebagai seorang sahabat dan memperhatikan segala kebutuhan anak, sehingga anak merasa dipenuhi dan di perhatikan oleh orang tua, dihargai dan menyenangkan (Alamiyah et al, 2021;Wardani et al, 2020;Wijayanti & Fauziah, 2020).…”
Section: Pendahuluanunclassified